Analisis Yuridis Putusan Hakim dalam Kasus Perceraian dengan Alasan Murtad - Rahmi, Nailur (Al-Qisthu, 2023)
The compilation of Islamic law has already stipulated that apostasy can be one of the grounds for divorce. However, in 2012, the Supreme Court of the Republic of Indonesia affirmed the decision of the Semarang Religious Court, which granted a divorce to a married couple, one of whom had apostatized. This affirmation was based not solely on proving continuous irreconcilable disputes but also disregarded the fact of the wife's apostasy. This article aims to provide an analysis of the case, emphasizing that the Supreme Court's decision could serve as jurisprudence for subsequent judicial rulings. The research employs a judicial case study approach, utilizing data from the Semarang Religious Court's decision Number 1449/Pdt.G/2011/PA.Sm, the Semarang Religious High Court's decision Number 043/Pdt.G/2012/PTA.Smg, and the Supreme Court's decision Number 742 K/AG/2012. The study indicates that the Supreme Court's affirmation of the Religious Court's decision is not a contradiction to the norms outlined in the Compilation of Islamic Law or Islamic jurisprudence. Rather, it aims to ensure the fulfillment of women's rights during and after the divorce process, such as past livelihood, mut'ah, and iddah allowances.